PUSAT KOMUNITAS BAGI LANSIA KALANGAN MENENGAH KEATAS - Alvian Tan; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2023)
Currently, 500 million people worldwide with an average age of 60 are suffering from depression in old age. In the year of 2000, there were 22.3 million elderly people in Indonesia with a life expectancy of 65 to 75 years. By 2020, with a life expectancy of 70 to 75 years, it increased by 11.09 percent (more than 29.12 million) and is projected to reach 1.2 billion by 2025. This research aims to provide design ideas for the elderly to feel comfortable and content by accommodating their needs for a community center for the elderly. This study was conducted using qualitative descriptive research method and design method based on phenomena. Through this research, it can be concluded that the design of a community center with a healing environment concept can be an alternative that helps the elderly overcome depression by applying the principles of a healing environment, which include determining appropriate programs for the elderly, such as a functional senior park, walking garden, communal area, creativity space, doctor's consultation room, health clinic, and open area designed with the principles of a healing environment, including independence, consciousness, connectedness, purpose, physical activities, and restorative elements. By creating an environment of a community center for the elderly, a sense of togetherness is fostered through interactions among the elderly, preventing depression caused by loneliness, which impacts both physical and psychological health. Keywords: community centre; depression; elderly Abstrak Saat ini, 500 juta orang di seluruh dunia dengan usia rata-rata 60 tahun menderita depresi di usia tua. Pada tahun 2000, terdapat 22,3 juta lansia di Indonesia dengan harapan hidup 65 sampai 75 tahun. Pada tahun 2020, dengan angka harapan hidup 70-75 tahun, meningkat menjadi 11,09 persen (29,12 juta lebih) dan diperkirakan mencapai 1,2 miliar pada tahun 2025. Penelitian ini bertujuan untuk memberikan ide perancangan untuk para lansia agar para lansia betah dan nyaman dengan mewadahi kebutuhan akan pusat komunitas para lansia. Penelitian ini dilakukan dengan menggunakan metode penelitian kualitatif deskriptif serta metode desain berdasarkan fenomena. Melalui penelitian ini dapat disimpulkan bahwa perancangan pusat komunitas dengan konsep healing environment dapat menjadi alternatif yang mampu membantu lansia dalam mengatasi depresi dengan menerapkan prinsip prinsip healing environment yang mencakup penentuan program yang sesuai dengan lansia, di antaranya functional senior park, walking garden, area komunal, creativity space, ruang konsultasi dokter, health clinic, dan open area yang dirancang dengan prinsip-prinsip healing environment, meliputi independence, consciousness, connectedness, purpose, physical activities, dan restorative. Dengan menciptakan lingkungan pusat komunitas lansia, tercipta rasa kebersamaan melalui interaksi orang lanjut usia dengan sebayanya supaya bisa terhindar dari depresi karena kesepian yang berdampak pada kesehatan fisik maupun psikis.